Исследование влияния ударной волны в зазоре шпура на полноту детонации шпурового заряда - Лабинский, К.Н. (Геотехнічна механіка, 2014)
В работе рассмотрены особенности распространения ударной волны в зазоре шпура при канальном эффекте. Уточнен механизм проявления канального эффекта, который действует на заряд ВВ при его детонации. Установлена критическая длина заряда ВВ в донной части шпура, на которой возможен отказ детонации, которая зависит от коэффициента заряжания и может находиться в пределах от 4,5% до 20% от его длины. У роботі розглянуті особливості розповсюдження ударної хвилі в зазорі шпуру при канальному ефекті. Уточнений механізм прояву канального ефекту, який діє на заряд ВР при його детонації. Встановлена критична довжина заряду ВР у донній частині шпуру, на якій можлива відмова детонації, яка залежить від коефіцієнта заряджання та може знаходитися у межах від 4,5% до 20% від його довжини. Specificities of the shock-wave propagation in the blast-hole gap at the channel effect are considered. A mechanism of the channel effect which impacts on the blast-hole charge at its detonation is specified. It is stated that when a time period of the excess ( more than critical) pressure action increases a diameter of the blasting agent can essentially decrease. In this case a defining factor is an impact of the external pressure on the charge detonation stability. A critical length of the blasting agent charge in the bottom of the blast-hole, where the breaking of the detonation is possible, is specified. This critical length of the charge depends of charging coefficient and can be in range from 4,5% to 20% of its full length.